A Comparative Study of Low-Level Laser Therapy and Transcutaneous Electrical Nerve Stimulation as an Adjunct to Pharmaceutical Therapy for Myofascial Pain Dysfunction Syndrome: A Randomized Clinical Trial - Arash Mansourian; Sara Pourshahidi; Maryam-Sadat Sad; Hooman Ebrahimi (Tehran University of Medical Sciences, 2019)
Objectives: Myofascial pain dysfunction syndrome (MPDS) is the most common form of temporomandibular disorders. Because of the multifactorial nature of the problem, its management usually involves several treatment modalities to maximize their synergistic effects. This randomized clinical trial aimed to assess the efficacy of low-level laser therapy (LLLT) and transcutaneous electrical nerve stimulation (TENS) as an adjunct to pharmaceutical therapy for treatment of MPDS. Materials and Methods: This clinical trial evaluated 108 MPDS patients. First, the initial pain intensity of patients was determined using a visual analogue scale (VAS). The first phase of the study included education, awareness, self-care, behavior and relaxation therapy. After 1 month, the pain score was measured again using VAS. Patients who acquired a pain score >1 were divided into three groups of LLLT with diode (GAAlAr) laser with 0.2 W power, TENS, and control, using block randomization. All groups received 10 mg fluoxetine once daily, 0.25 mg clonazepam once daily and 10 mg baclofen three times a day. ANOVA was used to compare the recovery rate of the three groups. Results: Pain in the trapezius muscle and pain on mouth opening resolved faster in the laser + medication group. The recovery rate was faster in the mean muscle pain, general pain reported by patients, pain in the masseter and pterygoid muscles and pain and limitation in lateral movements in both laser + medication and TENS groups. Conclusion: Combination of LLLT and TENS with medication accelerated pain relief and resolved movement restrictions in MPDS patients.